Curriculum education policies of the ministry of education and effective social sciences in secondary schools state level - Huánuco 2014 - Zevallos Fretel, Julio (2018)
Arrival research has the main purpose to know the impact of curricular educational policies ofthe Ministry of education in the validity of the social sciences in State educational institutions ofthe secondary level of Huanuco. For its execution have been used the methodological procedures,such as the documentary analysis, reading and bibliographical envelope curricular educationalpolicies related to social sciences. Opinion questionnaires have been related to the independent anddependent variable whose data have allowed us to develop the statistical tables for analysis and interpretation. The main findings are reflected in that to) the level of implementation of educationpolicy curriculum of the Ministry of education to schools in Regular basic education of secondaryeducation in the Huanuco region, have been little consistent in an average of 60% in the opinion ofteachers of the second specialty program of secondary education in teaching of public education ofthe UNHEVAL, as shown in the statistical results; (b) the level of entry into force of the social sciencesin institutions of education in Regular basic education of secondary education in the Huanuco region,have little validity in averaging 46,85% according to teachers of the second specialty program ofsecondary education in teaching of public education of the UNHEVAL, as shown in the statisticalresults; (b) the level of implementation of the social sciences in State educational institutions ofRegular basic education of secondary education in the Huanuco region, has been unsatisfactory in anaverage of 62.9% in the opinion of teachers of the second specialty program of secondary educationin teaching of public education of the UNHEVAL as shown in the statistical results; (c) curriculareducational policies of the Ministry of education and its level of validity and applicability of the socialsciences have not covered the expectations of the goals and targets proposed in State educationalinstitutions of the secondary level in the Huánuco region.